Epithelial barrier hypothesis in the context of nutrition, microbial dysbiosis, and immune dysregulation in metabolic dysfunction-associated steatotic liver - Cebi, Merve; Yilmaz, Yusuf (Frontiers in Immunology, 2025)
In recent years, the prevalence of chronic liver diseases, particularly Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD), has increased significantly. This upward trend is largely associated with lifestyle-related factors such as unhealthy dietary habits, physical inactivity, and various environmental influences. Among the key elements contributing to the pathogenesis of MASLD, the integrity of the intestinal epithelial barrier emerges as a critical determinant, given its central role in maintaining immune homeostasis along the gut-liver axis. Disruption of this barrier, often driven by excessive consumption of saturated fats and refined carbohydrates in combination with low dietary fiber intake, can lead to microbial dysbiosis. This imbalance in the gut microbiota triggers immune dysregulation and promotes systemic inflammation, thereby exacerbating hepatic injury. This review discusses the contribution of epithelial barrier dysfunction to the development and progression of MASLD, with a particular focus on how increased intestinal permeability may initiate and sustain chronic liver inflammation. Additionally, the influence of dietary and environmental factors on epithelial integrity, immune responses, and the inflammatory cascade is addressed. A better understanding of the complex interplay between gut barrier impairment, immune modulation, and liver pathology may offer valuable insights into MASLD pathophysiology and contribute to the development of more targeted therapeutic strategies.